2009
DOI: 10.3171/2009.3.spine08635
|View full text |Cite
|
Sign up to set email alerts
|

Anterior and posterior decompressive surgery for progressive amyotrophy associated with cervical spondylosis: a retrospective study of 51 patients

Abstract: Object The aims of this study were to review the clinicoradiological findings in patients who underwent decompressive surgery for proximal and distal types of muscle atrophy caused by cervical spondylosis and to discuss the outcome and techniques of surgical intervention. Methods Fifty-one patients (43 men and 8 women) with proximal (37, with arm drop) and distal muscle atrophy (14, with wrist drop) unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…On the other hand, a high signal intensity change on T2-weighted MRI was not associated with the neurological prognosis in patients who required conversion to surgery, similar to some previous studies. 16,17 There were several limitations to the present study that should be kept in mind when interpreting the results. First, the treatment protocol, including the observational follow-up period, indications for surgical treatment and the type of surgery were not unified in the patients, because this was a retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a high signal intensity change on T2-weighted MRI was not associated with the neurological prognosis in patients who required conversion to surgery, similar to some previous studies. 16,17 There were several limitations to the present study that should be kept in mind when interpreting the results. First, the treatment protocol, including the observational follow-up period, indications for surgical treatment and the type of surgery were not unified in the patients, because this was a retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulty in shoulder abduction, positive arm-drop sign, or positive wrist-drop sign is always found in patients with cervical spondylotic amyotrophy [30,46]. Recently, Ahdab et al [2] reported that a 65-year-old man with cervical spondylotic amyotrophy was referred for a dropped head syndrome because posterior neck and shoulder girdle muscles were atrophic.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Electromyographic changes in patients with anterior radix or nerve root injury are characterized by fibrillation and positive sharp waves, whereas fasciculation and synchronization are often significant electromyographic findings in motor neuron injury of the anterior horn. However, fasciculation and synchronization are evident in patients with cervical spondylotic amyotrophy [46]. Thus, the anterior horn and motor axons could be damaged in cervical spondylotic amyotrophy.In addition, evoked spinal cord potentials (ESCPs) and cervical motion evoked potentials (MEPs) are useful for diagnosing cervical spondylotic amyotrophy.…”
Section: Electrophysiologic Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Uchida et al reported that surgical outcome in patients with the distal type of muscle atrophy was inferior to outcome in patients with the proximal type, with the distal type being associated with less muscle power improvement. 12 Similarly, in our previous study, we reported that the distal type of CSA was a significant factor influencing a poor surgical outcome (in comparison with the proximal type of CSA).…”
mentioning
confidence: 99%